Current annealing and electrical breakdown of epitaxial graphene - Hertel, Stefan; Kißlinger, Ferdinand; Jobst, Johannes; Waldmann, Daniel; Krieger, Michael; Weber, Heiko B. (Applied Physics Letters, 2011)
We report on epitaxial graphene on silicon carbide at high current densities. We observe two distinguished regimes, and a final breakdown. First for low current densities the conductance is enhanced due to desorption of adsorbates. Second with increasing bias the sample locally starts to glow and is strongly heated. The silicon carbide material decomposes, graphitic material is formed and thus additional current paths are created. The graphene layer breaks down, which is, however, not visible in high bias data. The final breakdown is a self-amplifying process resulting in a locally destroyed sample but surprisingly with better conductance than the original sample. © 2011 American Institute of Physics.
UnivIS-Import:2015-04-14:Pub.2011.nat.dphy.IAP.LAP.curren